Estudio de prefactibilidad para la implementación de una planta para la producción de arroz con verduras cocido para microondas - Maravi Benavides, Alexandra Fiorella (2021)
The present pre-feasibility study for the implementation of a plant for the production of microwaveable cooked rice with vegetables aims to determine its technical and economic feasibility. The project meets the need for a nutritious and healthy food that is convenient and adapts to the lives of Lima's working population. It was determined that the target market is people of NSE A and B in the districts of zones 6 and 7 of Metropolitan Lima between the ages of 18 and 55. In addition, it was defined that the presentation would be in 250-gram pouches and the demand for the seventh year of operation would be 430 129 units. It was also decided that the best location would be in the district of Lurigancho-Chosica in the department of Lima. The calculated plant size is 430 129 units of final product. Similarly, it was determined that the NPV value is S/1 046 812,20, the EIRR value is 21,81%, the NPV value is S/1 025 127,05 and the IRR value is 25,24%, demonstrating the profitability of the project. Finally, Lurigancho-Chosica is identified as a zone of influence, since the plant will operate there and generate employment. As part of the quantitative analysis, an added value of S/3 492 107 was obtained for the seven years of the project.